2004
DOI: 10.1158/0008-5472.can-04-0129
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Active Site on the Laminin α5 Chain Globular Domain That Binds to CD44 and Inhibits Malignancy

Abstract: The laminin ␣5 chain is a component of laminin-10 (␣5␤1␥1) and -11 (␣5␤2␥1). In this study, we have screened 113 overlapping synthetic peptides from the laminin ␣5 globular domain (G-domain) for cell attachment activity with B16-F10 cells using peptide-coated dishes. Eleven attachment-active peptides were identified. In vivo experimental B16-F10 pulmonary metastasis and primary tumor growth assays found that 4 of the 11 peptides inhibited tumor metastasis and growth and increased apoptosis. These four peptides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(84 citation statements)
references
References 31 publications
3
80
1
Order By: Relevance
“…Laminins, which were found in blood vessels and in the glial limitants externa in glioma, were also shown to be expressed by human glioma cells positive for glial fibrillary astrocytic protein (GFAP) (Tysnes et al 1999). An active site on laminin which was capable of binding to CD44 was identified (Hibino et al 2004). In addition, Ljubimova et al (Ljubimova et al 2004) found that highly invasive GBMs overexpressed laminin-8, a member of the subset of laminins characterized by containing the alpha4 chain.…”
Section: Vasculature-associated Ecm Molecules Expressed By Gliomasmentioning
confidence: 99%
“…Laminins, which were found in blood vessels and in the glial limitants externa in glioma, were also shown to be expressed by human glioma cells positive for glial fibrillary astrocytic protein (GFAP) (Tysnes et al 1999). An active site on laminin which was capable of binding to CD44 was identified (Hibino et al 2004). In addition, Ljubimova et al (Ljubimova et al 2004) found that highly invasive GBMs overexpressed laminin-8, a member of the subset of laminins characterized by containing the alpha4 chain.…”
Section: Vasculature-associated Ecm Molecules Expressed By Gliomasmentioning
confidence: 99%
“…7 In melanoma cells, CD44 can bind the laminin a5 chain which results in inhibition of tumor cell migration, invasion and angiogenesis. 8 While the standard form of CD44 (CD44s) is ubiquitously expressed, the CD44v isoforms are highly restricted to processes like leukocyte activation, inflammation and malignant transformation (as reviewed by Herrlich et al 9 and Wittig et al 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of LN␣4-deficient mutant mice (lama4Ϫ/Ϫ) reveal that although ␣4-LNs are not required for blood vessel formation, they play important roles in blood vessel maturation, and in stabilization of vessels that form with injury, inflammation and tumor growth. 7,12,13 In vitro studies indicate that ␣4LNs directly regulate endothelial cell proliferation and inhibit apoptosis.…”
mentioning
confidence: 99%